鄰近傾斜岩石面對擋土牆主動土壓力之影響 - 方永壽; FANG YUNG-SHOW (My University, 2011)
本計劃研究鄰近傾斜岩石面對作用於擋土牆主動土壓力的影響。若一座重力式擋土牆頗 為接近傾斜岩石界面，牆後回填土受到岩石面邊界限制，因此牆後之主動土楔可能無法完全 的發展出來。在此狀況下，作用於擋土牆之主動土壓力可能與傳統Coulomb 及Rankine 理論 算出之的主動土壓力不同。本研究計畫將以試驗室實驗方式探討岩石界面傾斜角、及傾斜介 面底部與擋土牆間水平間距b 對牆面主動土壓力之影響。試驗中擋土牆是以平移方式逐漸移 離受限之回填土。所有的試驗都是在國立交通大學擋土牆試驗系統進行，模型擋土牆高 H=0.5m，以安裝於模型擋土牆上的土壓力計量測牆面之水平土壓力。 本研究將運用一雙向加勁鋼質介面板來模擬鄰近的傾斜岩石介面，本計畫擬進行試驗的 界面板位置包含下列狀況的組合: (1) b = 0, 50 mm, 100 mm, 150 mm, 250 mm , 350 mm, 500 mm, 及2,000 mm； (2)  = 0, 50o, 60 o, 70 o, 80 o 及90 o。所有實驗都採用氣乾渥太華砂為背填 土，本研究第一年採用空中霣降法備製均勻密度的疏鬆(Dr = 35%)砂土試體。從實務觀點考 慮，相對密度Dr = 35%是非常疏鬆的回填土，施工規範常要求承商將擋土牆後之回填土夯實 至相對密度Dr = 70% ~ 75%的緊密狀態。為了模擬現地狀況，本研究第二年將採用震動式平 板夯實機，在試驗室夯壓土壤至Dr = 75%。疏鬆與緊密砂土的應力應變關係及體積變化行為 皆有甚大之差異。Chen and Fang (2008)報告震動式土壤夯實會在緊砂內造成額外水平土壓 力，因此本研究將分兩年進行，分別探討疏鬆與緊密受限回填土引致之主動土壓力。以1g 物 理模型獲得之實驗結果，將與理論解、數值分析結果、及離心機試驗結果相互印證。期望本 研究之成果，能夠使大地工程師更加了解鄰近傾斜岩石介面對擋土牆主動土壓力的影響，因 此促成更安全、更合理、更經濟的擋土牆設計。

This study investigates the lateral earth pressure acting on a vertical rigid wall, which moves away from a constrained backfill of dry sand. The instrumented retaining-wall facility at National Chiao Tung University is used to investigate the effects of an adjacent inclined rock face on the development of active earth pressure. If the retaining wall is constructed adjacent to an inclined rock face, the stiff rock face might intrude the active soil wedge as the wall moves away from the backfill. Can the Coulomb and Rankine theories be used to estimate the active earth pressure on the wall with constrained backfill? Would the distribution of active earth pressure still be linear with depth? To correctly calculate the factor of safety against sliding and overturning of the wall, it is necessary for the designer to understand how would the nearby rock face influence the active earth pressure. The inclination angle of the rock face with the horizontal is defined as , and the horizontal spacing between the inclined rock face and the base of the wall is expressed as b. Considering the intrusion of the inclined rock face into the active soil wedge, the rock face inclination angles  = 0o, 50o, 60o, 70o, 80o, 90o and the horizontal spacing b = 0, 50 mm, 100 mm, 150 mm, 250 mm , 350 mm, 500 mm, and 2,000 mm will be tested. For all experiments, the surface of backfill is horizontal and the height of the backfill above the wall base H is 0.5 m. All of the earth-pressure experiments are conducted in the National Chiao Tung University retaining-wall facility. Horizontal earth pressure against the wall is measured with the soil-pressure transducers mounted on the model wall. A steel interface plate is designed and constructed to simulate the inclined rock face near the retaining wall. The plate and its supporting system will be developed to fit in the NCTU model retaining-wall facility. Air-dry Ottawa sand is used throughout this investigation. For the first year of this study, the backfill is deposited by air pluviation from the slit of a hopper into the soil bin. The relative density of soil achieved will be 35%. Note that the backfill with the relative density of 35% is a very loose material. In practice, the granular backfill behind a retaining wall is generally recommended to be compacted to achieve a relative density of 70-75%. From a practical point of view, in the second year of this study, the loose backfill will be compacted to a relative density of 75%. Experimental results obtained with this 1-g physical model tests will be compared with theoretical solutions, numerical findings and centrifuge test results. It is hoped that these results will enhance a better understanding regarding the influence of a nearby inclined rock face on the development of active earth pressure.
Active Earth Pressures on Retaining Walls Adjacent to Inclined Rock Faces
Keywords: 主動壓力; 受限背填土; 土壓力; 模型試驗; 擋土牆; 砂; Active pressure; Constrained backfill; Earth pressure; Model tests; Retaining wall; Sand